2020
DOI: 10.5336/mdethic.2019-71012
|View full text |Cite
|
Sign up to set email alerts
|

The Attitude of Individuals Admitted a Family Center About Organ Donation

Abstract: Bu çalışmada, bir aile sağlığı merkezine başvuran bireylerin organ bağışına ilişkin tutumlarının belirlenmesi amaçlandı. Gereç ve Yöntemler: Araştırma, tanımlayıcı kesitsel tipte uygulandı. Çalışmaya 582 birey alındı. Veri toplamada, araştırmacılar tarafından güncel literatür kullanılarak hazırlanan Tanıtıcı Bilgiler Formu ve Organ Bağışı Tutum Ölçeği kullanıldı. Bulgular: Çalışmaya alınan bireylerin %58,2'sinin organlarını bağışlamak istediği, ancak sadece %3,3'ünün organ bağış kartı olduğu, %37,8'inin organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…In contrast, Çam et al (2022) found that females had a higher level of positive attitude towards organ donation than males (Çam et al, 2022). Gürler and Topal (2020) investigated the attitudes to organ donation of individuals presenting at a family health centre, and reported that gender had no effect (Gürler & Topal, 2020). A potential explanation for these results could be the prescriptive nature of gender roles related to helping behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Çam et al (2022) found that females had a higher level of positive attitude towards organ donation than males (Çam et al, 2022). Gürler and Topal (2020) investigated the attitudes to organ donation of individuals presenting at a family health centre, and reported that gender had no effect (Gürler & Topal, 2020). A potential explanation for these results could be the prescriptive nature of gender roles related to helping behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The need for education to develop positive social behaviour and a positive attitude to organ donation has been reported in literature (Dumanli et al, 2019;Yücetin et al, 2003). By determining attitudes to organ donation, the factors affecting these attitudes, incorrect beliefs, and lack of information, education can be planned directed to these subjects, and by helping to develop a positive attitude to organ donation the number of organ donations can be increased (Gürler et al, 2020). In a study of medical faculty students by Yılmaz and Demirağ (2019), the main reason for students not wanting to donate organs was found to be lack of information, and it was shown that effective education would have a positive effect on the number of organ donations (Yilmaz & Demirag, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Bu çalışmada, diğer çalışmalarla (Oktem, ve diğerleri 2020, Rokade ve Gaikawad 2012) uyumlu olarak organ bağışında bulunma isteği beden bağışlama isteğinden fazla çıkmıştır. Yapılan bir çalışmada organ bağışında bulunmak ile artan eğitim düzeyi arasında anlamlı bir ilişki tespit edilmiştir (Gürler ve Hançer 2020). Anatomistlerle gerçekleştirilen bir çalışmada katılımcıların %20,5'i organ bağışında bulunduğunu, %49.4'ü ise ileride organlarını bağışlamayı düşündüklerini belirtmişlerdir (Sehirli, Saka ve Sarikaya 2004).…”
Section: Betül Kundaktepe and Mustafa Canbolat Sağlık Alanında Faaliy...unclassified
“…Araştırmalara göre organ bağışında bulunan veya bulunmak isteyen kişilerin transplantasyon süreci ve organ bağışı konularında daha fazla bilgi sahibi oldukları görülmektedir (1,5). Sağlık çalışanlarının organ bağışı konusunda hasta ve yakınlarını bilgilendirme ve yönlendirmedeki rolü toplumun organ bağışı konusundaki farkındalığını, olumlu tutumlarını ve dolayısıyla bağışlanan organ sayısını arttırmada önemlidir (3,6). Özellikle hemşirelerin organ bağışı ve nakli konusundaki bilgi düzeyleri, organ bağışına karşı olumlu tutumları ve gönüllülükleri, beyin ölümü gerçekleşmiş hastaya yaklaşımlarını ve ailesinin karar verme sürecini önemli derecede etkileyerek ailelerin organ bağışında bulunma oranlarını arttırabilir (7,8).…”
Section: Introductionunclassified